Usage of antimicrobials and effective microorganisms in broiler farms in the West Coast of Peninsular Malaysia - Yeo, Yee Hein (2015)
There is a rising concern of usage of antimicrobials in farms as they contribute to the emergence of antibiotic resistance. Effective microorganisms (EM) is one of the proposed alternatives to antimicrobials. The aim of this study was to investigate the usage of antimicrobials and EM in local broiler farms. A crosssectional survey was conducted in 24 randomly selected broiler farms in the West Coast of Peninsular Malaysia. All 24 farms use at least one antimicrobial agent, for both prophylaxis and treatment purposes. Amoxicillin (62.5%) is the most commonly used antimicrobial. Eight farms (33.3%) reported usage of EM. Out of the 8 farms, 5 farms (62.5%) reported usage of EM via spraying onto the feces of the chickens; while 3 farms (37.5%) added EM into the drinking water. Seven (87.5%) of the 8 farms reported a decrease in fecal odour due to the usage of EM; while 3 (37.5%) of the 8 farms reported drier chicken manure. This study indicated that antimicrobials are used more commonly as compared to EM in local broiler farms. There is a need for development of strategies to promote more rational and prudent use of antimicrobials, as well as the use of antimicrobial alternatives in local broiler farms.